PENGARUH PENERAPAN KEBIJAKAN TAX AMNESTY DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Ari Putra Wirawan, Ida Bagus Ngurah; Noviari, Naniek (E-Jurnal Akuntansi, 2017)
Taxes are state revenues that will be used for general financing such as development, education and health, even taxes are also one of the benchmarks of the success of a country's economy. The problems that often occur today are still many people who have not fulfilled their tax obligations. The purpose of this study was to analyze the effect of tax amnesty policy implementation and tax sanction on personal taxpayer compliance in KPP Pratama East Denpasar. Population in this research is all individual taxpayer registered in KPP Pratama East Denpasar. The number of samples in this study as many as 100 respondents in the area of ??East Denpasar. Sampling was done by using Accidental Sampling Method. Data analysis method used in this research by using multiple linear regression analysis, validity test, reliability test, classic assumption test, determination coefficient (test R2), model conformity test (F test) and t test. Based on the results of the research note that tax amnesty has a positive and significant effect on taxpayer compliance. This shows that if the tax amnesty increase, the taxpayer compliance rate will increase also. Tax sanctions have a positive and significant effect on taxpayer compliance. This shows that the higher the sanction of taxation then the level of taxpayer compliance will tend to be higher.